Mucormycosis and COVID-19: A Dual Curse - Vishal R. Tandon; Akhil Mahajan; Annil Mahajan (Dr. Annil Mahajan, 2021)
Mucormycosis is a serious, but rare opportunistic, invasive and life-threatening fungal infection primarily caused by Rhizopus arrhizus with very high case fatality. Recently, its alarming rise in the number among COVID-19 patients mostly with uncontrolled diabetes and those who received excessive administration of steroids for the treatment of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection has raised interest among the scientific community to learn more about the said disease. The current review describes, its epidemiology, clinical presentation, risk factors, warning signs, diagnostic test and available preventive and treatment modalities for its effective management.